2019
DOI: 10.18632/aging.101939
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-125b promotes resistance of glioma cells to TRAIL through overexpression of Tafazzin which is a mitochondrial protein

Abstract: Overexpression of Tafazzin (TAZ), a mitochondrial protein, is often observed in many cancers. However, the association between aberrant expression of TAZ and drug resistance remains unclear. The aim of this study is to explore the role of TAZ in regulating the TRAIL resistance in glioma. We thus established the TRAIL resistance models on glioma by using the U87 and U251 cell lines (U87/R and U251/R). As the results, obvious overexpression of TAZ was observed in U87/R and U251/R cells. However, knockdown of TAZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…resistance to sorafenib and carmustine [42][43][44]. MiR-125b was reported to be related with drug resistance of cetuximab [45], doxorubicin [46], cisplatin, TNFrelated apoptosis-inducing ligand [47]. Exosomal miR-125b was reported to be a predictive biomarker for mFOLFOX6-based chemotherapy in colorectal cancer patients [48].…”
Section: Agingmentioning
confidence: 99%
“…resistance to sorafenib and carmustine [42][43][44]. MiR-125b was reported to be related with drug resistance of cetuximab [45], doxorubicin [46], cisplatin, TNFrelated apoptosis-inducing ligand [47]. Exosomal miR-125b was reported to be a predictive biomarker for mFOLFOX6-based chemotherapy in colorectal cancer patients [48].…”
Section: Agingmentioning
confidence: 99%
“…TRAIL is a pro-apoptotic protein that starts the apoptosis process by binding to its death receptors DR4 and DR5, targeting tumor cells without attacking healthy cells [35][36][37]. For this reason, TRAIL has been considered a promising cancer therapy [16]; however, some studies have shown that gastric cancer cells are resistant to this apoptosis pathway [13,17,18,38].…”
Section: Discussionmentioning
confidence: 99%
“…For advanced glioma patients, systemic chemotherapy is main form of treatment 5 . However, drug resistance is still an important cause of chemotherapy failure in many cancers including glioma 6 , 7 . Therefore, it is an urgent problem to overcome the chemotherapy drug resistance in glioma.…”
Section: Introductionmentioning
confidence: 99%